Super edge trimagic total labeling of some star type graphs. (3rd April 2017) - Regees, M.
Abstract: A bijection such that for each edge uv ϵ E ( G ), the value of f ( u ) + f ( uv ) + f ( v ) is equal to either k 1 or k 2 or k 3 is called an edge trimagic total labeling of a ( p, q ) graph. In this paper we prove that the star type graphs admits edge trimagic total labeling and super edge trimagic total labeling.